IMMU-29. COMBINATION PD-1 BLOCKADE AND IRRADIATION OF BRAIN METASTASIS INDUCES AN EFFECTIVE ABSCOPAL EFFECT IN MELANOMA. (5th November 2018) - Pfannenstiel, Lukas; McNeilly, Corey; Xiang, Chaomei; Kang, Kai; Diaz, Claudia Marcela; Yu, Jennifer; Gastman, Brian
Abstract: Nearly half of melanoma patients develop brain metastases during the course of their disease. Despite advances in both localized radiation and systemic immunotherapy, brain metastases remain difficult to treat, with most patients surviving less than 5 months from the time of diagnosis. While both treatment regimens have individually shown considerable promise in treating metastatic melanoma, there is interest in combining these strategies to take advantage of potential synergy. In order to study the ability of local radiation and anti-PD-1 immunotherapy to induce beneficial anti-tumor immune responses against distant, unirradiated tumors, we used two mouse models of metastatic melanoma in the brain, representing BRAF mutant and non-mutant tumors. Combination treatments produced a stronger systemic anti-tumor immune response than either treatment alone. This resulted in reduced tumor growth and larger numbers of activated, cytotoxic CD8 + T cells, even in the unirradiated tumor, indicative of an abscopal effect. The immune-mediated effects were present regardless of BRAF status. These data suggest that irradiation of brain metastases and anti-PD-1 immunotherapy together can induce abscopal anti-tumor responses that control both local and distant disease.